Current Trends of Human Adenovirus Types Among Hospitalized Children—A Systematic Review - Janina Soler Wenglein; Luca Scarsella; Christine Kotlewski; Albert Heim; Malik Aydin (Viruses, 2025)
Human adenoviruses (HAdVs) are pathogens causing different illnesses, particularly in pediatric and immunocompromised patients in developed countries. The clinical spectrum of HAdV-infections ranges from mild to severe, and the clinical presentation varies widely. Certain HAdVs types, including types B3, E4, B7, B14, B21, G55, and B66, may be associated with lower respiratory tract infections and thus lead to higher hospitalization, increased morbidity, as well as lethality rates. The aim of this article is to synthesize and analyze the prevalence of specific HAdV types in pediatric patients worldwide. A systematic literature search was performed using MEDLINE, Scopus, and Web of Science. In total, n = 1167 titles and abstracts were screened, and 105 full-text articles were assessed for eligibility. Screening, data extraction, and appraisal were analyzed by reviewers, in accordance with PRISMA guidelines and JBI recommendations. We included studies reporting on currently circulating HAdV types (n = 16). Based on a systematic and narrative approach, relevant types of HAdV biology and infections in children are presented. In detail, HAdV-B3 and HAdV-B7 were commonly associated with severe respiratory tract infections, while HAdV-F40 and HAdV-F41 caused acute gastroenteritis. Moreover, detailed research revealed the critical role of HAdV-C2 and the necessity for particular attention to HAdVs in acute neurological infections. This comprehensive analysis highlights the significant global distribution and diverse clinical implications of different HAdV types in children, pointing out the need for continued surveillance to better understand HAdVs epidemiology and its implications for public health, and future preventive measures, in particular among vulnerable patients.